Mindhunter : inside the FBI's elite serial crime unit - Douglas, John E.; Olshaker, Mark, 1951- (Gallery Books, 2017)
"During his twenty-five year career with the Investigative Support Unit, Special Agent John Douglas became a legendary figure in law enforcement, pursuing some of the most notorious and sadistic serial killers of our time: the man who hunted prostitutes for sport in the woods of Alaska, the Atlanta child murderer, and Seattle's Green River killer, the case that nearly cost Douglas his life. As the model for Jack Crawford in The Silence of the Lambs, Douglas has confronted, interviewed, and studied scores of serial killers and assassins, including Charles Manson, Ted Bundy, and Ed Gein, who dressed himself in his victims' peeled skin. Using his uncanny ability to become both predator and prey, Douglas examines each crime scene, reliving both the killer's and the victim's actions in his mind, creating their profiles, describing their habits, and predicting their next moves."--Page [4] of cover.